How has microbiology changed 200 years after Pasteur’s birth? - Bikard, David (Comptes Rendus Biologies, 2022)
The last two centuries have seen major scientific and technological advances that have turned the field of microbiology upside down. If Louis Pasteur came out of his vault to celebrate his two hundredth birthday with us, would he recognize the field of study of which he was one of the founders? Are the objectives of the discipline still the same? What is the influence of new technologies on our scientific approach? What are the new horizons and future challenges?